Finite Element-Based Structural Evaluation of a Rescue Boat Crane Mount on LCT 153 Vessel - Rean, Everin Shafa Ghaitsa; Nugroho, Priyambodo Nur Ardi; Sofia, Emy (Universitas Negeri Jakarta, 2025)
Rescue operations onboard marine vessels rely on effective and reliable deployment mechanisms for rescue boats, particularly in emergency scenarios. Cranes are commonly installed to assist in lowering rescue boats, but their performance depends greatly on the strength and reliability of their mounting systems. This study investigates the structural performance of a rescue boat crane mounting system on an LCT 153 vessel using finite element analysis. The problem addressed in this research is the lack of quantitative data on how different crane configurations affect the structural integrity of their mounting base under operational loads. Two crane models with different outreach and load specifications were assessed to identify the most structurally efficient option. Stress distribution and deformation were simulated using 3D models and meshed at various sizes to ensure convergence accuracy. The results revealed that the configuration with a 6-meter outreach generated lower stress (19.69 MPa) and deformation (0.004 mm), while the 7-meter alternative showed higher values. The findings contribute to safer and more efficient crane mounting designs and serve as a reference for shipyards in selecting appropriate equipment based on load performance and structural reliability.